Advances in pharmacogenomics of antiretrovirals: an update. (September 2007) - Ma, Qing; Brazeau, Dan; Forrest, Alan; Morse, Gene D
Recent developments in the pharmacogenomics of antiretroviral drugs provide new prospects for predicting the efficacy of treatment and potential adverse effects. HIV/AIDS is a serious but treatable infectious disease, yet current treatment is limited by high rates of adverse drug reactions and development of resistance due to suboptimal drug concentrations in a significant proportion of patients. Antiretroviral therapy is especially suitable for pharmacogenomic investigation as both drug exposure and treatment response can be quantified and certain adverse effects can be assessed with validated measures. Additionally, there is increasing knowledge of the pharmacokinetics and dynamics of antiretroviral drugs, and some candidate genes implicated in the metabolism, transport and adverse effects have been identified. However, recent studies of the association of particular genes and their genetic variants with HIV management and adverse drug reactions have not provided unifying conclusions. This article reviews the most recently published work and summarizes the state of research in this area. Future directions for research and the application of this technology to the clinical practice of individualizing treatment for HIV management are discussed.